2005
DOI: 10.1002/ana.20338
|View full text |Cite
|
Sign up to set email alerts
|

Microglial activation and dopamine terminal loss in early Parkinson's disease

Abstract: Neuroinflammatory glial response may contribute to degenerative processes in Parkinson's disease (PD). To investigate changes in microglial activity associated with changes in the presynaptic dopamine transporter density in the PD brain in vivo, we studied 10 early-stage drug-naive PD patients twice using positron emission tomography with a radiotracer for activated microglia [(11)C](R)-PK11195 and a dopamine transporter marker [(11)C]CFT. Quantitative levels of binding potentials (BPs) of [(11)C](R)-PK11195 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

30
542
2
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 734 publications
(580 citation statements)
references
References 39 publications
30
542
2
1
Order By: Relevance
“…It has been reported that inflammation is up-regulated in brains of PD patients (McGeer et al, 1988;Whitton, 2007), and parallel changes in microglial activation and corresponding dopaminergic terminal loss are observed in the affected nigrostriatal pathway of early PD (Ouchi et al, 2005). Despite some controversial findings, the beneficial effects of non-aspirin and nonsteroidal antiinflammatory drugs (NSAIDs) on PD progression have been supported by several epidemiological studies (Chen et al, 2003;Hernan et al, 2006;Ton et al, 2006), suggesting that antiinflammatory agents may prevent neuronal death in PD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that inflammation is up-regulated in brains of PD patients (McGeer et al, 1988;Whitton, 2007), and parallel changes in microglial activation and corresponding dopaminergic terminal loss are observed in the affected nigrostriatal pathway of early PD (Ouchi et al, 2005). Despite some controversial findings, the beneficial effects of non-aspirin and nonsteroidal antiinflammatory drugs (NSAIDs) on PD progression have been supported by several epidemiological studies (Chen et al, 2003;Hernan et al, 2006;Ton et al, 2006), suggesting that antiinflammatory agents may prevent neuronal death in PD.…”
Section: Introductionmentioning
confidence: 99%
“…The neuronal protective effect of NSAIDs has been supposedly achieved through the inhibition of cyclooxygenase (COX)-2 that subsequently reduce toxic mediators (such as inflammatory cytokines and oxidants) derived from activated microglia, which have been observed in the affected substantia nigra pars compacta of PD patients (McGeer et al, 1988;Ouchi et al, 2005). However, up-regulation of COX-2 has been found not only in microglia but also in neurons of substantia nigra pars compacta of PD patients and mice intoxicated by 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) (Liberatore et al, 1999;Teismann et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…TNFα is produced by activated microglia and the number of activated microglial cells are increased in the brains of parkinsonian patients (McGeer and McGeer 1997). Microglia are already activated during the early phase of Parkinson's disease, and the presence of activated microglia is correlated with decrease in dopamine nerve fiber density (Ouchi et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Both [ 11 C](R)-PK11195 and [ 11 C]PK11195 have been used as positron emmision tomography (PET) tracers to study activated microglia in various neurologic disorders. It has been used to study stroke (Ramsay et al, 1992;Pappata et al, 2000;Gerhard et al, 2000Gerhard et al, , 2005a), Alzheimer's disease (Groom et al, 1995; Cagnin et al, 2001a;Versijpt et al, 2003), multiple sclerosis (Banati et al, 2000;Debruyne et al, 2002Debruyne et al, , 2003Versijpt et al, 2005) and various other diseases (Pappata et al, 1991; Banati et al, 1999Banati et al, , 2001Goerres et al, 2001;Cagnin et al, 2001bCagnin et al, , 2004Cicchetti et al, 2002;Gerhard et al, 2003Gerhard et al, , 2004Gerhard et al, , 2005bTurner et al, 2004Turner et al, , 2005Venneti et al, 2004;Henkel et al, 2004;Ouchi et al, 2005). Most studies have used a reference tissue approach to quantify binding, either by applying the simplified reference tissue model (SRTM) (Lammertsma and Hume, 1996) or by using uptake normalized to a reference region.…”
mentioning
confidence: 99%